Information and Communication Technology Proceedings of ICICT 2016 (Advances in Intelligent Systems and Computing,, 2018)
This book volume contains 31 papers presented at ICICT 2016: Second International Congress on Information and Communication Technology. The conference was held during 12-13 December 2016, Bangkok, Thailand and organized communally by G R Foundation, and Computer Society of India Division IV - Communication and Division V - Education and Research. This volume contains papers mainly focused on ICT for computation, algorithms and data analytics, and IT security.